Prediction of portal dosimetry quality assurance results using log files-derived errors and machine learning techniques - Lew, Kah Seng; Chua, Clifford Ghee Ann; Koh, Calvin Wei Yang; Lee, James Cheow Lei; Park, Sung Yong; Tan, Hong Qi (Frontiers in Oncology, 2023)
This work aims to use machine learning models to predict gamma passing rate of portal dosimetry quality assurance with log file derived features. This allows daily treatment monitoring for patients and reduce wear and tear on EPID detectors to save cost and prevent downtime. Using gamma passing rate of 1%/1mm criteria and entire dataset, LASSO regression has a R2 of 0.121±0.005 and RMSE of 4.794±0.013%, SVM regression has a R2 of 0.605±0.036 and RMSE of 3.210±0.145%, Random Forest regression has a R2 of 0.940±0.019 and RMSE of 1.233±0.197%. XGBoost regression has the best performance with a R2 and RMSE value of 0.981±0.015 and 0.652±0.276%, respectively. Log file-derived features can predict gamma passing rate of portal dosimetry with an average error of less than 2% using the 1%/1mm criteria. This model can potentially be applied to predict the patient specific QA results for every treatment fraction.